Using Microcontrollers for High Accuracy Analogue Measurements - Jaanus, M.; Udal, A.; Kukk, V.; Umbleja, K. (Elektronika ir Elektrotechnika, 2013)
Paper discusses some cost-efficient and convenient solutions for the microcontroller-based voltage measurements. Microcontrollers offer several flexible possibilities to modify the reference voltage, to switch between different amplification/attenuation coefficients or to add a necessary bias to the measured voltage. Five unconventional methods are described that have been used in scientific experimental research and/or distant learning toolkits to enhance the accuracy of the built-in analogue to digital converters of ordinary microprocessors. DOI: http://dx.doi.org/10.5755/j01.eee.19.6.4559